Strategi Pencegahan Dan Penanggulangan Penyalahgunaan Narkoba Melalui Pendekatan Komunitas Di Kabupaten Sidenreng Rappang - Pannyiwi, Rahmat; Ali, Akhwan; Yulis, Dian Meiliani (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
Drug abuse is a serious problem that threatens the health, safety, and future of young people in Indonesia. Sidenreng Rappang Regency is an area vulnerable to drug distribution and abuse, particularly among adolescents and the productive population. This study aims to identify strategies for preventing and addressing drug abuse through a community approach. The research method used a qualitative descriptive approach with in-depth interviews, observation, and documentation of government officials, community leaders, health workers, law enforcement officers, and community groups. The results indicate that community-based strategies include: drug education and counseling, strengthening the role of families, cross-sector collaboration (government, the National Narcotics Agency, police, schools, and community organizations), and the formation of drug-aware communities. In conclusion, drug prevention efforts through a community approach are effective in raising awareness, strengthening family resilience, and creating a conducive, drug-free environment. The research recommendations include expanding the scope of educational programs, optimizing the role of local communities, and integrating drug prevention policies with regional development programs.